Kajian Laju Infiltrasi Pada DAS Air Timbalun Kota Padang Ditinjau Dari Perbedaan Lithology, Kemiringan Lahan, dan Parameter Fisik Tanah - Ahmad Fauzan; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. Infilration that is disturbed in an area will affect the existing hydrological cycle and make the natural balance not met. The construction and opening of new land has led to a diversion of land use which was originally a water catchment area, so that the water catchment area was reduced, causing flooding in residential areas. Infiltration is also influenced by several factors including rock lithology conditions, land slope and soil physical condition. Therefore, it is necessary to study the infiltration rate, infiltration zoning mapping, and the calculation of water discharge that can be applied to the soil. This research was carried out at 15 different points. The data obtained are primary data which is direct observation in the field, namely the coordinates of the study location, groundwater data, lithology, land slope, soil physical properties (water content, porosity, saturated hydraulic conductivity, soil density), and infiltration rate measurement data. Based on data processing using the Kostiakov method, the average infiltration rate of the study area was 0.010565 cm/min, including the very low absorption area classification (<0.1-0.2 cm/min). based on statistical analysis, rock lithology conditions, land slope and soil physical properties are very influential on the rate of infiltration. Infiltration zoning mapping was divided into 6 zones, with the lowest infiltration rate 0.000017093-0.002509782 cm/minute and the highest infiltration rate zone 0.022775581-0.046821598 cm /minute. In addition, the water discharge that can be absorbed by the soil in the study area with an area of 14,199 km2 is 6,600 m3/hour/km2 (very low). Keywords: Infiltration Rate and Infiltration Zone , Kostiakov Method, Rocks Lithology, Land Slope, Soil Physical Characterist